Does education affect religiosity? Causal evidence from a conservative emerging economy - Mustafa Özer; Jan Fidrmuc; Emmanouil Mentzakis; Özcan Özkan (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
Does education make people more or less religious? The previous literature offers mixed findings on the relationship between education and religiosity. This may be due to endogeneity bias: education and religiosity can be caused by a third variable such as culture or upbringing. We instrument education by exposure to the 1997 education reform in Türkiye which increased mandatory schooling from 5 to 8 years. The schooling reform increased the probability that young girls would complete 8 years of schooling and report lower religiosity later in life. The reform apparently did not influence such outcomes for boys. These effects are observed primarily for females growing up in strongly religious or poor areas.
urn:nbn:fi-fe202402228380
Keywords: H52; I26; J10; Z12; 330; Education; religiosity; 2SLS; gender; social norms; Türkiye